2012
DOI: 10.1071/rd11268
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of an in vitro system to study maternal communication with spermatozoa

Abstract: In vivo, gamete maturation, fertilisation and early embryonic development take place inside the oviduct. Several studies have indicated that local responses towards gametes and embryos are generated by the maternal reproductive tract. However, no defined in vitro model currently exists to allow detailed and systematic investigation of maternal communications with gametes and embryos. Therefore, we characterised an in vitro model based on the interaction of boar spermatozoa with an immortalised porcine oviduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…The observation made herein, that HSP gene expression is only markedly upregulated when spermatozoa are in direct contact with OECs rather than when they are kept separate using diffusible membrane inserts, tends to support this view. In agreement with other studies (Aldarmahi et al, 2012, 2014), we thus propose that spermatozoa binding directly to OECs in co‐culture activates a specific signal transduction pathway within the OECs that results in the upregulation of HSP gene expression. HSPs synthesized de novo in response to sperm appear to translocate from within OECs to the oviductal lumen (Georgiou et al, ) and interact directly with the sperm membrane, probably through cholesterol molecules and/or lipid rafts that are present/accessible in uncapacitated but not in capacitated spermatozoa (Moein‐Vaziri et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observation made herein, that HSP gene expression is only markedly upregulated when spermatozoa are in direct contact with OECs rather than when they are kept separate using diffusible membrane inserts, tends to support this view. In agreement with other studies (Aldarmahi et al, 2012, 2014), we thus propose that spermatozoa binding directly to OECs in co‐culture activates a specific signal transduction pathway within the OECs that results in the upregulation of HSP gene expression. HSPs synthesized de novo in response to sperm appear to translocate from within OECs to the oviductal lumen (Georgiou et al, ) and interact directly with the sperm membrane, probably through cholesterol molecules and/or lipid rafts that are present/accessible in uncapacitated but not in capacitated spermatozoa (Moein‐Vaziri et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…or nonbiological (e.g., glass‐beads) entities on chaperone/HSP gene expression by OECs. Notwithstanding, existing evidence suggests that OECs do respond to the presence of both spermatozoa and oocytes by altering the abundance of the proteins they secrete, although the exact alterations are cell‐type specific (Georgiou et al, 2005, 2007; Kodithuwakku et al, ; Aldarmahi et al, 2012, 2014). The observation made herein, that HSP gene expression is only markedly upregulated when spermatozoa are in direct contact with OECs rather than when they are kept separate using diffusible membrane inserts, tends to support this view.…”
Section: Discussionmentioning
confidence: 99%
“…All primers were tested for specificity using National Center for Biotechnology Information (NCBI) blast (http://blast.ncbi.nlm.nih.gov/Blast.cgi, accessed 1 January 2011) and for primer-dimer and secondary structure using the DNA analysis tools on the integrated DNA technology website (http://eu.idtdna.com/scitools/scitools.aspx, accessed 1 January 2011). Primers for b-actin (BACT), ADM, HSPA8 and PGES were designed from the DNA sequence of Sus scrofa species, as described previously (Aldarmahi et al 2012). The efficiencies of the reference and targets genes were assessed and determined.…”
Section: Primer Designmentioning
confidence: 99%
“…Some studies report that the level of mRNA expression is altered with increasing culture passage number and presume that dedifferentiation of differentiated cells takes place in vitro after several cell culture passages (Neumann et al 2010). In a previous study, we demonstrated that expression of adrenomedullin (ADM), heat shock 70 kDa protein 8 (HSPA8) and prostaglandin E synthase (PGES) in an immortalised oviductal epithelial cell line decreased as the number of oviductal culture passages increased (Aldarmahi et al 2012). However, it was not clear whether the variation between different cell passages was affected by the handling of cells on different experimental days and/or altered in response to coculture with spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated that these cells could be used to study spermatozoa-oviduct epithelial cell interactions because this cell line is not dedifferentiated and has not lost the expression of functional receptors (Hombach-Klonisch et al 2006). Additionally, when these cells are incubated with spermatozoa, the alteration in the expression of some genes (ADM, HSPA8 and PGES) is similar to what was described for primary oviductal epithelial cells (Aldarmahi et al 2012). Spermatozoa-oviductal epithelium binding assays evaluate the plasma membrane for multiple functions before the fertilisation process (Waberski et al 2005), and this in vitro binding test has proven to be very useful for the assessment of sperm quality given its high sensitivity for detecting differences (De Pauw et al 2002;Petrunkina et al 2007).…”
Section: Discussionmentioning
confidence: 71%